Innovation in SMEs: Behavioural Patterns in Portugal - Fernandes, Silvia Brito (2014)
The globalisation has fostered new temporal and spatial relations that reach an increasing scope with the support of information and communication technologies. These global changes are reflected on the local systems of production, requiring more competitiveness from them. Here it is vital the role of SMEs (Small and Medium Enterprises) for their flexibility and local embeddedness. This is a crucial factor of propensity for instituting regional innovation systems that promote regional development through local complementaries.